Kesuksesan Kemoterapi Multiobat untuk Rabdomiosarkoma pada Wanita Usia Tujuh Tahun: Laporan Kasus - Abdullah, Arwini Avissa; Ridha, Nadirah Rasyid (Universitas Islam Negeri Alauddin Makassar, 2024)
The most frequent soft tissue cancer in children is rhabdomyosarcoma (RMS). A diagnosis typically occurs between the ages of 5 and 6 in women. We report a seven-year-old girl was referred to Hospitals with complaints of a protruding left eye. The swelling was presented in July 2021, which was small earlier but has increased and become more prominent. An examination of the left eyelid showed a 2.5 x 2.5 x 1.5 cm solid mass with edema, erythema, and secretion in the superior and inferior affected eyelid. A Head CT scan revealed a left superolateral lacrimal duct tumour with a normal intracerebral structure. The histopathology examination found dacryoadenitis with an RMS tumour. This patient was treated using the RMS multidrug chemotherapy protocol (vincristine, actinomycin, and cyclophosphamide) for three sessions, which decreased tumour progressivity five months later. Early and appropriate treatment of this patient with chemotherapy regimens according to the protocol for RMS has a good prognosis.